Replacement of the C6ORF66 Assembly Factor (NDUFAF4) Restores Complex I Activity in Patient Cells - Dana Marcus; Michal Lichtenstein; Ann Saada; Haya Lorberboum-Galski (BMC, 2013)
Abstract Disorders of the oxidative phosphorylation (OXPHOS) system frequently result in a severe multisystem disease with the consequence of early childhood death. Among these disorders, isolated complex I deficiency is the most frequently diagnosed, accounting for one-third of all cases of respiratory chain deficiency. We chose to focus on complex I deficiency, caused by mutation in the assembly factor chromosome 6, open reading frame 66 (C6ORF66; NADH dehydrogenase [ubiquinone] complex I assembly factor 4 [NDUFAF4]) protein. We used the approach of cell- and organelle-directed protein/enzyme replacement therapy, with the transactivator of transcription (TAT) peptide as the moiety delivery system. This step will enable us to deliver the wild-type assembly factor C6ORF66 into patient cells and their mitochondria, leading to the proper assembly and function of complex I and, as a result, to a functional OXPHOS system. We designed and constructed the TAT-ORF fusion protein by gene fusion techniques, expressed the protein in an Escherichia coli expression system and highly purified it. Our results indicate that TAT-ORF enters patients' cells and their mitochondria rapidly and efficiently. TAT-ORF is biologically active and led to an increase in complex I activity. TAT-ORF also increased the number of patient cells and improved the activity of their mitochondria. Moreover, we observed an increase in ATP production, a decrease in the content of mitochondria and a decrease in the level of reactive oxygen species. Our results suggest that this approach of protein replacement therapy for the treatment of mitochondrial disorders is a promising one.